1971
DOI: 10.1111/j.1532-5415.1971.tb02626.x
|View full text |Cite
|
Sign up to set email alerts
|

Male Nursing Home Patients: Relocation and Mortality*

Abstract: The effect of transfer from one nursing home to another was studied in 82 male veterans over a four-year period. Group T comprised 41 patients who were transferred from the initial nursing home to one or more other homes; Group NT (controls) comprised 41 patients who were not transferred from the initial nursing home. Disability and illness were assessed by specific rating scales, and the 32 nursing homes were evaluated by three social workers. There were no significant differences between the two groups of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Of the interinstitutional relocation studies examining mortality rates, the study by Ogren and Linn (1971) was an important departure from previous research. An increase in mortality rate associated with a transfer was not identified in this study; rather, a decrease was identified.…”
Section: Mortalitymentioning
confidence: 99%
“…Of the interinstitutional relocation studies examining mortality rates, the study by Ogren and Linn (1971) was an important departure from previous research. An increase in mortality rate associated with a transfer was not identified in this study; rather, a decrease was identified.…”
Section: Mortalitymentioning
confidence: 99%
“…Yet, in a recent review of 17 studies investigating the cognitive status vulnerability hypothesis, Mirotznik and Los Kamp (2000) found 12 studies lacked a comparison group of nonmovers (Aldrich, 1964;Friedman et al, 1995;Guttman & Herbert, 1976;Kral, Grad, & Berenson, 1968;Lander et al, 1997;Lieberman & Tobin, 1983, pp. 151-152;Markus, Blenkner, Bloom, & Downs, 1972;Marlowe, 1974;Miller & Lieberman, 1965;Nirenberg, 1983;Ogren & Linn, 1971). Without a comparison group, one cannot rule out the possibility that the greater mortality and/or morbidity among relocated residents who are cognitively impaired may merely reflect the fact that such residents deteriorate at a higher rate in general, regardless of the occurrence of relocation (Coffman, 1983;van Dijk, Dippel, & Habbema, 1991).…”
mentioning
confidence: 99%
“…it is impossible to study nursing home preferences by observing movement of patients from facilities with which they are dissatisfi ed to other facilities. There is some evidence to suggest, however, that the widely known negative effects of relocation of nursing home patients does not occur when the patient himself has requested transfer and is prepared for the move (44).…”
Section: Measuring Quality Of Lifementioning
confidence: 99%